CALCULATION, COLLECTION, REPORTING, AND FULFILLMENT OF VALUE-ADDED TAX OBLIGATIONS ON PT. KHOERINDO MAKMUR: PERHITUNGAN, PEMUNGUTAN, PELAPORAN DAN PEMENUHAN KEWAJIBAN PAJAK PERTAMBAHAN NILAI PADA PT. KHOERINDO MAKMUR - Feby Nurshafa; Yanti Budiasih (Yayasan Education and Social Center, 2021)
This article aims to analyze and examine the correctness of the calculation and reporting as well as filling in the VAT period SPT based on Law number 11/2020. The type of data obtained is qualitative, and the data sources used are primary data and secondary data. The research technique used is a qualitative descriptive approach. The data analysis technique used is data collection to then draw conclusions. The results show that PT. Khoerindo Makmur has performed calculations in accordance with tax regulations based on Law number 11/2020, but in reporting and depositing PT. Khoerindo Makmur hasn’t been in accordance with the appropriate date in the tax regulations